Current concepts in carpal instability: anatomy, classification and management. Issue 4 (August 2021) - Burton, Robert; Reay, Emma
Abstract: Carpal instability is a complex subject and the theories behind the pathoanatomy and management continue to evolve in the literature. The consequences of carpal instability for the patient can be significant and lead to functional impairment and long-term pain. We outline the normal anatomy of the carpus and relate the complex interactions between the ligamentous and bony structures to the patterns of injury both acute and chronic. We then go on to review current opinion on the classification, assessment and management of patients with carpal instability.